Analysis on Biometrics, Forensics Protecting Using Key Binding Mode Based Ppbss Using Fuzzy Vault - Javid Basha, Syed; Muni Hema Kumar, B (International Journal of Computer Sciences and Engineering, 2025)
Direct storage of biometric templates in databases exposes the authentication system and legitimate users to numerous security and privacy challenges. Human beings can no longer be separated from electronic devices and the Internet technology. The need for information made available on systems and networks which are connected on the internet. It is very essential to provide an effective security measure and system that ensures the confidentiality, integrity, and availability of information system, networks, and the services and resources made available. In this paper a new way of technique is Fuzzy vault. Fuzzy Vault is one of the most promising bio-cryptographic techniques to prevent the template data from being misused. To make the fuzzy vault practically realizable in real-life applications especially for large databases, the chaff generation time needs to be reduced to greater extent. This work focuses on decreasing the chaff generation time to reduce the overall vault creation time This can be achieved using Biometric and Digital Forensic Technology.